Nursery Growing Media: Agronomic and Environmental Quality Assessment of Sewage Sludge-Based Compost - Barbara De Lucia; Giuseppe Cristiano; Lorenzo Vecchietti; Elvira Rea; Giovanni Russo (Applied and Environmental Soil Science)
There is a stringent need to reduce the environmental impact of peat in the plant nursery production chain. In this experiment, the use of different rates of sewage sludge compost in the preparation of growing media for potted Bougainvillea was evaluated to assess its efficiency for the replacement of peat and to quantify the environmental impact of such alternative substrates by the life cycle assessment (LCA) method. Five substrates containing increasing proportion of composted sewage sludge to peat (0%, 25%, 40%, 55%, and 70% v/v) were used, and their physicochemical properties were measured. Bougainvillea plant growth, biomass production, and macro- and micronutrient absorption were also determined. The main results were that compost addition improved the plant nutrient and increased the substrate pH, electrical conductivity (EC), and dry bulk density values. Globally, the results showed that compost could be used at up to 55% by volume with no negative effects on plant growth. The LCA showed that use of compost reduced the environmental loads of the growth media, except the Global Warming Potential value (GWP100). Environmental implications of the use of compost in the plant nursery chain are discussed.